Optimalisasi Fungsi Pengawasan DPRD Terhadap PERDA di Kabupaten Padang Lawas Utara - Yahya Sentosa (Jurnal Smart Hukum (JSH), 2022)
Supervision of the implementation of regional regulations has an important meaning. The party that plays a role in supervision at the regional level is the DPRD. This study aims to determine the regulation of the Regional House of Representatives in implementing the law, position and function based on Law Number 23 of 2014 concerning Regional Government, to analyze and find out the Regional Regulations of North Padang Lawas Regency concerning Regional Levies, to analyze and determine the supervision of the House of Representatives. North Padang Lawas Regional People Against North Padang Lawas Regency Regional Regulation Number 12 of 2010 concerning Regional Levies. This study uses a normative juridical and empirical juridical method with a legal approach and a conceptual approach. The regulation of the position and function of DPRD in Law No. 23 of 2014 is as a regional legislative and executive. The implementation of the North Padang Lawas Regional Regulation Number 12 of 2010 concerning Regional Levies has not played a sufficient role in increasing the APBD. In order for the collection of regional retributions to be realized properly, the North Padang Lawas Regency Regional Regulation No. 12 of 2010 was amended with the North Padang Lawas Regency Regulation No. 3 of 2020. Supervision of the Padang Lawas DPRD against the North Padang Lawas Regency Regional Regulation Number 12 of 2020 concerning Regional Levies aims to understand what went wrong for future improvement and direct all activities in the context of implementation rather than a plan so that maximum results can be expected. Its essence helps that targets can be achieved early to avoid the occurrence of irregularities, abuse of authority, waste and leakage of development funds.